2012
DOI: 10.1063/1.3693334
|View full text |Cite
|
Sign up to set email alerts
|

Fluid transport in nanochannels induced by temperature gradients

Abstract: We investigate the mechanisms of fluid transport driven by temperature gradients in nanochannels through molecular dynamics simulations. It is found that the fluid-wall interaction is critical in determining the flow direction. In channels of very low surface energy, where the fluid-wall binding energy ε fw is small, the fluid moves from high to low temperature and the flow is induced by a potential ratchet near the wall. In high surface energy channels, however, the fluid is pumped from low to high temperatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 29 publications
1
18
1
Order By: Relevance
“…As for the high surface energy, the coupling strength of the water-graphene binding energy is relatively strong and the water-graphene interaction is mainly in the form of pressure drop along the x direction due to the coupling of surface effect, temperature gradient, and elastic collisions. 42 Furthermore, the velocity increases with the temperature gradient attributed to the increase in the pressure drop induced by the rise in temperature gradient.…”
Section: Resultsmentioning
confidence: 99%
“…As for the high surface energy, the coupling strength of the water-graphene binding energy is relatively strong and the water-graphene interaction is mainly in the form of pressure drop along the x direction due to the coupling of surface effect, temperature gradient, and elastic collisions. 42 Furthermore, the velocity increases with the temperature gradient attributed to the increase in the pressure drop induced by the rise in temperature gradient.…”
Section: Resultsmentioning
confidence: 99%
“…Similar observations have been already reported in the literature. 15 The variation of mean velocity of fluid inside the (10, 10) CNT with fluid-fluid interaction strength, ε ff , is shown in Fig. 15.…”
Section: Cntsmentioning
confidence: 99%
“…The interaction parameters, ε Ar−Ar = 0.0098 eV and σ Ar = 3.47 Å were used for liquid argon. 15 For C-C interaction in the CNT, ε C−C = 0.0037 eV and σ C = 3.4 Å were used as LJ parameters. 22 ε C−C = 0.024 eV and σ C = 3.34 Å were used as LJ parameters for C-C interactions in graphene.…”
Section: Simulation Detailsmentioning
confidence: 99%
See 1 more Smart Citation
“…(1) has been m odified by incorporating a disjoining pressure [16] or colum n resistance [17], It has been shown that the infiltration pressure depends on the surface properties, tem perature, and geom etry o f nanopores [11,12,14,15,[19][20][21][22][23], M olecular dynam ics sim ulations have m ainly been used to study how the pore size and tem perature affect the fluid infiltration in CN Ts, w here the surface properties are invariant [11,12,21,22], The general effects o f surface properties have been exam ined by experim ents, w hich have dem onstrated that p\"{ can be changed through surface treatm ent; however, the detailed dependence o f p mt on the surface properties or contact angle still rem ains unknow n [19,20]. O ur previous w ork on the flows in nanochannels reveals that the m olecular interactions betw een fluid m olecules and wall atom s play a critical role and m ake the classic N avier-Stokes equation invalid in certain conditions [6,24,25]. Given the fluid, such m olecular interactions are m ainly dependent on the surface energy, w hich is also expected to be im portant in affecting the fluid infiltration into nanochannels because the fluid contact angle is largely determ ined by the surface energy.…”
Section: Introductionmentioning
confidence: 97%